A label-free platform for dopamine biosensing. (January 2018) - Navarro, Jesús; Galbán, Javier; Marcos, Susana de
Aim: This work presents a label-free platform for dopamine (DA) monitoring based on the spectroscopic properties of laccase.Results: Working in batch mode, DA ranging from 25 to 250 μM, can be determined without the interference of norepinephrine and epinephrine. Laccase immobilized in a polyacrylamide film is the basis of a platform for the label-free determination of DA. The linear range goes from 100 to 900 μM with an RSD of 5.3% and a film lifetime of more than 30 measurements. The biosensors also permit the DA + epinephrine + norepinephrine determination.Conclusion: The method permits the determination of DA and the total concentration of the three neurotransmitters, and could be used for DA monitoring in urine samples.